Non-Shia practices of Muḥarram in South Asia and the Diaspora: beyond mourning - Sohoni, Pushkar; Tschacher, Torsten (Taylor & Francis Group, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- Notes on contributors -- List of figures -- Preface -- Chapter 1 Introduction -- Chapter 2 Ḥusayn's Hindu defenders -- Chapter 3 An ethnographic exploration of Muḥarram(s) in Pune, Maharashtra -- Chapter 4 Visual language of piety and power: Ta'ziahs and temples in the Western Deccan -- Chapter 5 The idea of religion and the criminalisation of Muḥarram in the Straits Settlements, 1830-1870 -- Chapter 6 Contestation and transformation: Mu ḥ arram practices among Sunni Muslims in South Africa, 1860-2020 -- Chapter 7 'It ain't religion -- it's just culture, man!' Muḥarram controversies in the Indo-Caribbean diaspora -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Muharram; Südasien